Perspectives on the Use of Transthoracic Echocardiography Results for the Prediction of Ventricular Tachyarrhythmias in Patients with Non-ischemic Cardiomyopathy - N. N. Ilov; D. R. Stompel; S. A. Boytsov; O. V. Palnikova; A. A. Nechepurenko (Столичная издательская компания, 2022)
Aim. To perform a comparative analysis of indicators of transthoracic echocardiography (TE), to establish echocardiographic predictors and their predictive role in the occurrence of stable ventricular tachyarrhythmia (VT) paroxysms in patients with nonischemic chronic heart failure (HF) and cardioverter-defibrillator (ICD) implanted for primary prevention of sudden cardiac death.Material and Methods. A prospective study was carried out, which included 166 patients with nonischemic HF at the age of 54 (49; 59) years with the left ventricle ejection fraction (LV EF) ≤35% and an ICD implanted. The observation time was 24 months. The primary endpoint was the first-ever stable paroxysm of VT (lasting for ≥30 seconds), detected in the «monitor» zone of VT, or paroxysm of VT, which required ICD therapy.  A total of 34 TE indicators were evaluated. Chi-square, Fischer, Manna-Whitney, single-factor logistic regression (LR), and multi-factor LR were used for data processing and analysis and for predictive modelling. Model accuracy was estimated using 4 metrics: ROC curve area (AUC), sensitivity, specificity and diagnostic efficiency.Results. During the two-year observation, 32 patients (19.3%) had a primary endpoint. The average time of occurrence of a stable VT episode was 21.6±0.6 months (95% confidence interval [CI] 20.5-22.8 months). The value of LV end-systolic dimension was the only parameter independently associated with VT (odds ratio 2.8 per unit increase, 95% CI 1.04-7.5; p=0.042). The complex analysis of echocardiographic indicators made it possible to identify 5 factors with the greatest predictive potential, which are linearly and nonlinearly related to occurrence of VT. These included the LV end-diastolic and end-systolic volumes, LV mass, index of relative LV wall thickness, upper-lower size of the right atrium. The metrics of the best predictive model were: AUC - 0.71 0.069 with 95% CI 0.574-0.843; specificity 50%, sensitivity 90.9%; diagnostic efficiency 57.1%.Conclusion. The study made it possible to evaluate the possibilities of the results of TE in predicting the probability of VT occurrence in patients with nonischemic HF and reduced LV EF. Predictive indicators have been identified that can be used to stratify the arrhythmic risk in the exposed cohort of patients.